An explanatory review of mandatory task - Hong S.G.K.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Behavioral research; Intelligent agents; Intelligent robots; Robotics; Software agents; goal; goal deliberation; mandatory task; Potential problems; Prioritization process; Robotic vacuum cleaners; Software agent technology; Task complexity; Multi agent systems